2006
DOI: 10.1590/s0074-02762006000800014
|View full text |Cite
|
Sign up to set email alerts
|

Morphological studies in a model for dengue-2 virus infection in mice

Abstract: One of the main difficulties in studying dengue virus infection in humans and in developing a vaccine is the absence of a suitable animal model which develops the full spectrum of dengue fever, dengue haemorrhagic fever, and dengue shock syndrome. It is our proposal to present morphological aspects of an animal model which shows many similarities with the dengue infection in humans. BALB/c mice were intraperitoneally infected with non-neuroadapted dengue virus serotype 2 (DENV-2). Histopathological and morphom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 40 publications
6
27
0
Order By: Relevance
“…Balb/c mice are susceptible to DENV and provide a convenient animal model of DENV infection (Barth et al, 2006;Paes et al, 2005Paes et al, , 2009). In the present study, intravenous infection of DENV in Balb/c mice resulted in detected levels of viral RNA, viral proteins and infectious viral particles.…”
Section: Denv Infection Induces Liver Injury In Balb/c Micementioning
confidence: 99%
See 2 more Smart Citations
“…Balb/c mice are susceptible to DENV and provide a convenient animal model of DENV infection (Barth et al, 2006;Paes et al, 2005Paes et al, , 2009). In the present study, intravenous infection of DENV in Balb/c mice resulted in detected levels of viral RNA, viral proteins and infectious viral particles.…”
Section: Denv Infection Induces Liver Injury In Balb/c Micementioning
confidence: 99%
“…The result from this study and from others suggest that intravenous injection system is the good route of administration of DENV in Balb/c mice, as DENV antigens were detected, which is in contrast to the subcutaneous injection system, in which DENV antigens could not be easily detected (Franca et al, 2010). Balb/c mice have been used to study liver injury during DENV infection (Barth et al, 2006;Paes et al, 2005Paes et al, , 2009. Liver damage was more severe in the intravenous injection as compared to the intraperitoneal injection (Barth et al, 2006;Paes et al, 2005Paes et al, , 2009).…”
Section: Denv Infection Induces Liver Injury In Balb/c Micementioning
confidence: 99%
See 1 more Smart Citation
“…A study from the DENV-2 infected mouse model have revealed that focal alterations in the liver along with the infection, In addition to this, ultra structural observations disclosed the alerted hepatocytes [27]. In this model dengue virus antigen was detected in the hepatocytes and thus is associated with the altered liver functions [27]. It has recently been understood that dengue infected dendritic cells activate other cells via direct contact mediated mechanism as evident that, dendritic cells activate natural killer cells via the mechanism however its mechanism of disease is not yet properly known [28].…”
mentioning
confidence: 89%
“…Another important study have described that, the secreted form of dengue virus non-structural protein NS1 is engulfed by hepatocytes, that further accumulate in the endosomes showing an important mechanism for the development of dengue associated pathophysiology [14]. A study from the DENV-2 infected mouse model have revealed that focal alterations in the liver along with the infection, In addition to this, ultra structural observations disclosed the alerted hepatocytes [27]. In this model dengue virus antigen was detected in the hepatocytes and thus is associated with the altered liver functions [27].…”
mentioning
confidence: 96%